NILAI TEOLOGI DALAM GURINDAM DUA BELAS RAJA ALI HAJI - Nurliana Nurliana (STIU Al-Mujtama Pamekasan, 2019)
Abstract: The sentence a good is the sentence of monotheism, all sayings that call upon virtue and prevent from evil and good deeds. The sentence good is like a shady tree bearing heavy fruit, its roots are blasted into the earth and its roots soar into the sky, that is the benefit of a sentence that contains truth. A good sentence can be used as a shelter for people who are overheated and can also provide fresh fruit for the well-being of life, giving guidance to look at the vast sky to realize the greatness of Allah. owner of the universe. Gurindam Dua Belas by Raja Ali Haji, contributes positively and is useful to humanity, especially Muslims in living their lives, so that the Gurindam Dua Belas is important to examine and understand its meaning in the form of theological values. Because it contains deep theological values ​​that are more educational and directed so that they can be implemented in everyday life. The discussion of theological values ​​(Values ​​Theology) in Gurindam Dua Belas Raja Ali Haji as an offer of study in this paper. The theological values ​​in Gurindam Dua Belas provide an understanding of the need for religion as a human nature and a foundation for the happiness of basic life in understanding theology, behavior, norms and rules of society. By understanding and practicing the religion of Islam and understanding the theological values ​​in the Gurindam Dua Belas human life will be directed to the truth so that life can avoid conflict and will feel the birth and inner calm towards worldly happiness and ukhrawi.Keyword: Value, theology, Gurindam.